The impact of social enterprises on local development - Petrescu, Claudia; Stănilă, Gabriel (Calitatea Vieții, 2012)
The purpose of this paper is to present and examine the role that social economy entities play in local and regional development in Romania. The type of services provided by the social economy entities, the effects thereof on the community, determine the major role such entities play within the local development process. This paper presents the partial results of a research conducted in Romania by the team of the project “PROMETEUS – Promoting social economy in Romania through research, education and training at European standards”. The research combined quantitative and qualitative research methods, so that it was able to capture in a comprehensive manner the social economy field at national level. The social enterprises are, in most of the cases, the motor of the local development, through the activities which they develop. The characteristics of these entities – the non-profit character, the social purpose of the activity, the participation of the members in the government, the multistakeholder governance – allow these organizations to mobilize local resources, to stimulate the creation of social capital at the level of the community, to ensure the welfare of the members of the community.